2008
DOI: 10.1038/nmeth.1177
|View full text |Cite
|
Sign up to set email alerts
|

A secreted luciferase for ex vivo monitoring of in vivo processes

Abstract: Luciferases are widely used to monitor various biological processes. Here, we describe the naturally secreted Gaussia luciferase as a highly sensitive reporter for quantitative assessment of cells in vivo by measuring its levels in blood. The Gluc blood assay complements in vivo bioluminescence imaging which has the ability to localize the signal and provides a multifaceted assessment of cell viability, proliferation and location in experimental disease and therapy models.Luciferase-mediated bioluminescence im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
335
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(349 citation statements)
references
References 12 publications
(2 reference statements)
12
335
0
1
Order By: Relevance
“…Tail vein blood was collected daily and used for Gaussia luciferase quantification by luminometry assay as previously described (16). Gaussia luciferase substrate was purchased through Targeting Systems.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Tail vein blood was collected daily and used for Gaussia luciferase quantification by luminometry assay as previously described (16). Gaussia luciferase substrate was purchased through Targeting Systems.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…The detection of Gaussia luciferase in whole animals can be easily accomplished using CCD-cameras. 48,77 In addition, it has been demonstrated that Gaussia luciferase secreted from tumor cells can be harvested from the blood and urine of mice 78 suggesting that the feasibility of a system that allows the detection and monitoring of autophagic pathways in whole animals by harvesting body fluids. Such a system could also be applied in animals bearing experimental tumors that have been engineered to express the sensor.…”
Section: Conclusion and Outlook: In Vivo Analysis Of Autophagymentioning
confidence: 99%
“…Indeed, the Huh-7.5/EG(4A/4B)GLuc cell line combines the advantages of the previously reported Huh7-J20 and Huh-7.5/EG(D4B5A)SEAP cell lines while also retaining the unique features of the Gaussia reporter. These specialized features can be enumerated: (i) as Gaussia is naturally secreted into the media, no cell lysis is required for the detection of its enzymatic activity; (ii) the secreted indicator function not only permits multiple kinetics experiments using only one culture through the sequential sampling of the medium, but also allows the cells to be used for other purposes, such as RNA extraction, Western blot analysis, and other assays; (iii) Gaussia is non-toxic and very potent -compared to the humanized forms of firefly (hFLuc) and Renilla (hRLuc) luciferases expressed under similar conditions, the humanized form of Gaussia (hGLuc) generates over a 1000-fold higher bioluminescent signal intensity from live cells (in concert with their immediate environment) and over a 100-fold higher intensity from viable cells alone (not including secreted luciferase) or cell lysates [21]; (iv) Gaussia is stable in culture medium (with a half-life ,6 d) [30] and samples can thus be stored at 4uC for several days without any significant change in its activity levels; (v) it is HCV genotype-independent, and therefore does not require any genetic modification of the viral genomes, due to the highly conserved nature of the NS3/4A recognition sequence [31].…”
Section: Discussionmentioning
confidence: 99%